THE ROLE OF INDONESIAN ONLINE MARKETPLACES IN INTELLECTUAL PROPERTY RIGHTS INFRINGEMENTS: A COMPARATIVE ANALYSIS - Lu Sudirman; Hari Sutra Disemadi (Jurnal Pembaharuan Hukum, 2023)
This research explores the forms of intellectual property rights violations and their causes, which are examined using the Indonesian intellectual property rights legal framework, to then generate an overview of the legal reconstruction needed to protect existing intellectual property in Indonesian online marketplaces. This research used normative legal research method with comparative approach by analyzing the existing Indonesian IP legal framework and compare it with other countries that are more advanced in IPR protections. This research puts a great emphasis on legal problems and the criminal elements of the Indonesian intellectual property rights legal framework to explain the position of online marketplaces and their responsibilities to also support the protection of IP and the growth of e-commerce overall. This research finds that Indonesia is facing normative issues in defining the role of online marketplace in many IP infringement cases. This finding is important in the support for continued legal development in Indonesia, to provide better protection of many forms of intellectual property rights in Indonesian online marketplaces.